DNA Uptake by the Nosocomial Pathogen Acinetobacter baumannii Occurs during Movement along Wet Surfaces - Wilharm, Gottfried (American Society for Microbiology, 2013)
The emergence of Acinetobacter baumannii as an increasingly multidrug-resistant nosocomial pathogen largely relies on acquisition of resistance genes via horizontal gene transfer. Here, we demonstrate that many clinical isolates of A. baumannii take up DNA while they move along wet surfaces. We show that both motility and DNA uptake are abolished after inactivation of pilT, which putatively encodes the type 4 pilus (T4P) retraction ATPase, and comEC, which putatively encodes the DNA uptake channel, respectively. Inactivation of pilT correlates with an increase in the number and length of pili with an average diameter of 7.2 nm. In the Galleria mellonella infection model, the comEC mutant is significantly attenuated, whereas the pilT mutant is not, dissecting biologically distinct roles of T4P and the DNA uptake channel. Collectively, these findings promote our understanding of the mechanisms of DNA uptake and resistance development in A. baumannii, which may also apply to other important pathogens.